The levels of vancomycin in the blood and the wound after the local treatment of bone and soft-tissue infection with antibiotic-loaded calcium sulphate as carrier material. (November 2017) - Wahl, P.; Guidi, M.; Benninger, E.; Rönn, K.; Gautier, E.; Buclin, T.; Magnin, J-L.; Livio, F.
Abstract : Aims: Calcium sulphate (CaSO4 ) is a resorbable material that can be used simultaneously as filler of a dead space and as a carrier for the local application of antibiotics. Our aim was to describe the systemic exposure and the wound fluid concentrations of vancomycin in patients treated with vancomycin-loaded CaSO4 as an adjunct to the routine therapy of bone and joint infections. Patients and Methods: A total of 680 post-operative blood and 233 wound fluid samples were available for analysis from 94 implantations performed in 87 patients for various infective indications. Up to 6 g of vancomycin were used. Non-compartmental pharmacokinetic analysis was performed on the data from 37 patients treated for an infection of the hip. Results: The overall systemic exposure remained within a safe range, even in patients with post-operative renal failure, none requiring removal of the pellets. Local concentrations were approximately ten times higher than with polymethylmethacrylate (PMMA) as a carrier, but remained below reported cell toxicity thresholds. Decreasing concentrations in wound fluid were observed over several weeks, but remained above the common minimum inhibitory concentrations for Staphylococcus up to three months post-operatively. Conclusion: This study provides the first pharmacokinetic description of the local application of vancomycin with CaSO4 as a carrier, documenting slow release, systemic safety and a release profile far more interesting than from PMMA. In particular, considering in vitro data, concentrations of vancomycin active against staphylococca l biofilm were seen for several weeks. Cite this article: Bone Joint J 2017;99-B:1537–44.